2011
DOI: 10.1371/journal.pone.0020150
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 Is a Component of the Transcriptional Network Regulated by GSK-3 in Quiescent Cells

Abstract: BackgroundThe protein kinase GSK-3 is constitutively active in quiescent cells in the absence of growth factor signaling. Previously, we identified a set of genes that required GSK-3 to maintain their repression during quiescence. Computational analysis of the upstream sequences of these genes predicted transcription factor binding sites for CREB, NFκB and AP-1. In our previous work, contributions of CREB and NFκB were examined. In the current study, the AP-1 component of the signaling network in quiescent cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…We further analyzed c-Jun protein levels, since c-Jun expression has been shown to be regulated by canonical Wnt signaling through a TCF/LEF binding motif on its endogenous promoter, which is truncated in the pJC6 reporter (12). Based on reports in the literature, induction of quiescence results in a reduction of c-Jun (46,47), and this was observed even with coexpression of both MEF2C and ␤-catenin (act) (Fig. 4C, left panel).…”
Section: Resultsmentioning
confidence: 99%
“…We further analyzed c-Jun protein levels, since c-Jun expression has been shown to be regulated by canonical Wnt signaling through a TCF/LEF binding motif on its endogenous promoter, which is truncated in the pJC6 reporter (12). Based on reports in the literature, induction of quiescence results in a reduction of c-Jun (46,47), and this was observed even with coexpression of both MEF2C and ␤-catenin (act) (Fig. 4C, left panel).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that GSK3 inhibits the activation of JNK and p38 (54) and is also involved in the inhibition of c-jun-mediated transcription (28). For example, it has been suggested that AP-1, CREB, and NF-kB form an integrated transcriptional network largely responsible for maintaining repression of genes downstream of GSK3 signaling (55). It should also be mentioned that GSK3 phosphorylates c-jun targeting this protein for degradation (56).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, ChIP assays indicated that c-Jun and JunD but not JunB were bound to predicted AP-1 sites upstream of eight of the GSK-3-repressed genes. 37 The binding of c-Jun increased in response to both PDGF stimulation and direct GSK-3 inhibition, whereas the binding of JunD was unaffected, suggesting a direct effect of GSK-3 on c-Jun. In addition, targeted siRNA knockdown confirmed that c-Jun is required for the induction of three genes following GSK-3 inhibition.…”
Section: Ap-1mentioning
confidence: 94%
“…in quiescent T98G cells, 37 as their expression requires growth factor signaling. [38][39][40][41] In contrast, c-Jun, JunD and JunB were all expressed in quiescent cells, and, therefore, were considered as candidate targets for regulation by GSK-3.…”
Section: Ap-1mentioning
confidence: 99%